Mendeley Management Reference Application and Scientific Writing Strategy - Muhammad Isradi; Yusra Aulia Sari; Andri Irfan Rifai; Amrun Rosyid; Abdul Hamid; Joewono Prasetijo (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
The main obstacle in making a scientific paper is due to lack of experience in writing and weak knowledge of strategies in technical writing. This workshop aims to provide insight into writing strategies, train using the Mendeley application reference tool, and write citations in journals or scientific papers. This activity was carried out through the Zoom Meeting application by presenting competent resource persons and divided into several stages, starting from participant registration, education stages and direct practice of using applications on Microsoft Office Word. From the training results, ten universities with 150 participants participated, of which 52% of participants were unfamiliar with the Mendeley application. With the evaluation results, 70.47% of participants were able to operate this application. Participants stated that they were very interested in using the simple regression results, the R2 value = 0.9691, and the ease of use of the application obtained an R2 value of 0.9702.